Sustainable Architectural Design of the Residential Compound Towers in Aleppo City Using the Genetic Algorithm: التصميم المعماري المستدام للأبراج السكنية التراكبية في مدينة حلب باستخدام الخوارزمية الجينية - Samer Mohamed Saleh Trissi, Mohamed Najib Kayali, Ahmed Haj Darwish (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2021)
This research aims to find innovative design solution to create sustainable compound residential towers in Aleppo city, for the reconstruction phase, by using the concept of sustainability and benefiting from natural energy sources. International organizations and many countries are interested in applying sustainable architecture standards, reducing emissions, mitigating pollution, and reducing long- term operating costs for buildings by making the most of natural resources. Tower buildings are among the most important design models that have been subject to the concepts of sustainability and their applications, due to their consumption of large amounts of energy. This research presents a study of a sustainable design for a residential compound tower, for the reconstruction phase in Aleppo city, using the genetic algorithm within the Grasshopper program. The tower design Idea depends on developing and linking the basic design idea of ​​the project with main design determinants such as dimensions, heights and other variables, including location and climatic characteristics, and then creating a barometric chart for these connections within the Grasshopper program. This chart links to the Galapagos tool, which is responsible for running the genetic algorithm. The random structure is generated when the algorithm started, and as a result of the cross- breeding, more advanced generations are created. The process continues to reach the most appropriate environmentally sustainable form to reduce the heat load acquired in summer. The model is evaluated environmentally using Ladybug simulation software, to provide solutions for modular residential towers that fit the local environment of Aleppo city. The results of the research showed that the solar heat load was reduced by adopting the genetic algorithm to find the most suitable configuration for the tower. The amount of reduction is 35% between the initial solutions and the final approved solution. The research also revealed that the use of green roofs reduces the heat load by 20%. The research also showed the effect of using shading facades. On the southern, western and eastern directions, the heat gain was reduced by 5%.